Answer:
A = Distributive Property of Multiplication
B = Addition Property of Equality
C = Subtraction Property of Equality
Step-by-step explanation:
Given:
5(2x - 1) = 9x + 2
The first step is to use the distributive property and multiply 5 to both numbers inside the brackets. So, A will be Distributive property of multiplication, which will result in:
5(2x) - 5(1) = 9x + 2
10x - 5 = 9x + 2
The next step is to add 5 on both sides of the equation. So, B will be the Addition property of equality, which will result in:
10x - 5 + 5 = 9x + 2 + 5
10x = 9x + 7
The next step is to subtract 9x from both sides of the equation. So, C will be the Subtraction property of Equality, which will result in:
10x - 9x = 9x + 7 - 9x
x = 7